Дослідження підходів формування економічного потенціалу підприємства у контексті транспарентності розвитку інвестиційних процесів - Ареф’єва О. В.; Ковальчук А. М.; Загайна С. Ю. (НТУ "ДП", 2023)
Результати. У статті досліджено сучасні підходи до формування економічного потенціалу підприємства в контексті транспарентності розвитку інвестиційних процесів. Розглянуто теоретико-методологічні підходи до трактування поняття «економічний потенціал підприємства». Визначено основні ознаки еволюційності поняття «економічний потенціал підприємства». Виявлено основні властивості економічного потенціалу підприємства у контексті транспарентності розвитку інвестиційних процесів, а саме: цілісність, складність, ієрархічність, здатність до розвитку, адаптивність, комунікативність. Виокремлено основні джерела розвитку економічного потенціалу підприємства. Проаналізовано підходи до формування економічного потенціалу підприємства (системний, комплексний, функціональний, інноваційний, інтеграційний, стратегічний, нормативний) та обґрунтовано доцільність застосування кожного із них при дослідженні підходів формування економічного потенціалу підприємств. Results. The article studies modern approaches to the formation of economic potential of the enterprise in the context of transparency of investment processes development. Some interpretations of the concept of "economic potential of the enterprise" are considered. The main signs of the evolution of the concept of "economic potential of the enterprise", in particular, the need to carry out activities in conditions of increasing transparency are defined. The main properties of the economic potential of the enterprise in the context of transparency of the development of investment processes are revealed: integrity, complexity, hierarchy, possibility of development, adaptability, communicability. Some sources of economic potential development are given. The analysis of approaches to the formation of economic potential of the enterprise is carried out: systemic, complex, functional, innovative, integration, strategic, normative and others. The expediency of application of each of them is substantiated. Complex conditions of internal and external environment of enterprises functioning are the reason for the constant search for the formation and development of economic potential.
Research of approaches to formation of economic potential of an enterprise in the context of transparency of investment processes
Keywords: підприємство; транспарентність розвитку; економічний потенціал; підходи до формування потенціалу підприємства; інвестиційні процеси; enterprise; transparency of development; economic potential; approaches to formation of enterprise potential; investment processes